Bifunctional catalyst for ultra-long-life low-temperature zinc-air battery
By using the A1-x-y-zBxCyDzO2 catalyst with a specific composition, the problem of insufficient activity of existing low-temperature bifunctional oxygen electrocatalysts is solved, and the efficiency and life of zinc air batteries at low temperatures is significantly improved.
Patent Information
- Application Number
- CN202411941398.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The existing low-temperature dual-function oxygen electrocatalysts are insufficient in the OER and ORR processes, resulting in low efficiency and short life of zinc air batteries in low temperature environments.
A1-x-y-zBxCyDzO2 is used as a bifunctional catalyst, where A and B are selected from certain metal elements, and C and D are selected from other metal elements. A catalyst with excellent electrocatalytic properties is formed through specific compositional proportions and preparation methods.
The catalyst exhibits excellent ORR and OER performance at low temperatures, significantly improving the performance and life of zinc air batteries at low temperatures.
Smart Images

Figure HDA0005212633400000011 
Figure HDA0005212633400000012 
Figure HDA0005212633400000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a dual-function catalyst for ultra-long-life low-temperature zinc-air batteries. Background Art
[0002] The construction of a new energy system based on renewable energy (wind energy, solar energy, etc.) requires the participation of efficient large-scale energy storage technology. Rechargeable zinc-air batteries (RZABs) are the next generation of efficient energy conversion and storage electrochemical energy storage batteries with high energy density (1086Wh kg -1 ), low-cost raw materials, high safety and other advantages, showing great application prospects in the field. However, the slow OER and ORR processes on the air electrode severely limit the efficiency of RZABs during the charge and discharge process, and lead to a limited cycle life of the battery, especially in low temperature environments.
[0003] At present, a series of bifunctional oxygen catalysts have been developed, including alloys, single-atom catalysts, metal oxides / sulfides / phosphides / hydroxides, etc. and their complexes. This is because working at low temperatures places higher requirements on catalysts. The slower electrochemical kinetics at low temperatures are not conducive to the reaction of oxygen-containing species on active sites. Existing low-temperature bifunctional oxide catalysts are mostly single-atom catalysts based on carbon materials, and most of them are solid-state flexible batteries, which not only have low energy efficiency, but also cannot operate stably under large currents. The OER activity of these catalysts is still poor, and the carbon materials are prone to corrosion, which seriously affects the life of the battery. In summary, there is still a lack of an ORR / OER bifunctional catalyst that has both high activity and stability and can drive low-temperature RZABs to operate. Summary of the invention
[0004] In view of this, the purpose of the present invention is to overcome the shortcomings of the current bifunctional oxygen electrocatalyst system and provide a method for preparing a bifunctional catalyst for an ultra-long life low-temperature zinc-air battery. The method has the characteristics of low cost, environmental friendliness and easy large-scale production. The obtained catalyst has very excellent electrocatalytic oxygen reduction (ORR) and oxygen evolution (OER) performance. At the same time, the zinc-air battery using this catalyst as the positive electrode exhibits good performance at low temperatures.
[0005] In the first aspect of the present invention, the present invention provides a low-temperature zinc-air battery bifunctional catalyst. According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst comprises A 1-x-y-z B x C y D zO2, wherein A and B are independently selected from one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Sn, Ga, Ge, C and D are independently selected from one of Pt, Ir, Ru, Pd, Au, Ag, In, Sb, Tl, Pb, Bi, Nb, Mo, Cd, wherein 0≦x<1, 0≦y<1, 0≦z<1, 0≦1-xyz<1, and at most one of x, y, z and 1-xyz is 0. The catalyst has excellent electrocatalytic oxygen reduction (ORR) and oxygen evolution (OER) performance, and the zinc-air battery using the catalyst as the positive electrode exhibits good performance at low temperatures.
[0006] According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst may further include at least one of the following additional technical features:
[0007] According to an embodiment of the present invention, the content of A is 0-99.9at%, the content of B is 0-99.9at%, the content of C is 0-99.9at%, and the content of D is 0-99.9at%, and at most one of the contents of A, B, C, and D is 0at%.
[0008] According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst is selected from MoSnMnIr metal oxide, MnFeIrSb metal oxide, CoFeRuIr metal oxide, CoSnRuBi metal oxide, VCoPdRu metal oxide, CoGaPdIr metal oxide, CuCoSbPt metal oxide or CuCoRuPt metal oxide.
[0009] In another aspect of the present invention, the present invention also proposes a method for preparing a low-temperature zinc-air battery bifunctional catalyst. According to an embodiment of the present invention, the method comprises:
[0010] 1) mixing a metal precursor salt solution and a solution consisting of an ammonium salt and a sugar to obtain a mixed solution;
[0011] 2) heating the mixed solution to obtain a porous material;
[0012] 3) The obtained porous material is calcined to obtain the low-temperature zinc-air battery bifunctional catalyst. The method has the characteristics of low cost, environmental friendliness and easy large-scale production. The obtained catalyst has very excellent electrocatalytic oxygen reduction (ORR) and oxygen evolution (OER) performance. At the same time, the zinc-air battery using the catalyst as the positive electrode shows good performance at low temperature.
[0013] According to an embodiment of the present invention, the method may further include at least one of the following additional technical features:
[0014] According to an embodiment of the present invention, the ammonium salt is one or more selected from ammonium bicarbonate, ammonium carbonate, thiourea, ammonium chloride, urea and ammonium sulfate.
[0015] According to an embodiment of the present invention, the ammonium salt is ammonium bicarbonate and ammonium carbonate.
[0016] According to an embodiment of the present invention, the ammonium salt is urea and ammonium carbonate.
[0017] According to an embodiment of the present invention, the ammonium salt is urea and ammonium chloride.
[0018] According to an embodiment of the present invention, the ammonium salt is ammonium bicarbonate and ammonium chloride.
[0019] According to an embodiment of the present invention, the ammonium salt is ammonium bicarbonate and urea.
[0020] According to an embodiment of the present invention, the sugar is selected from one of starch, lactose, galactose, sucrose, fructose, glucose and maltose.
[0021] According to an embodiment of the present invention, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:1-1:100.
[0022] According to an embodiment of the present invention, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:5-1:20.
[0023] According to an embodiment of the present invention, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:20, 1:15, 1:10, 1:8 or 1:5.
[0024] According to an embodiment of the present invention, the mixing process is performed by magnetic stirring, mechanical stirring or ultrasound.
[0025] According to an embodiment of the present invention, the concentration of the metal precursor salt solution is less than or equal to 100 mg / mL.
[0026] According to an embodiment of the present invention, the concentration of the metal precursor salt solution is 8 mg / mL, 9 mg / mL, 10 mg / mL, 15 mg / mL or 20 mg / mL.
[0027] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is (NH4)6Mo7O 24 4H2O, SnCl2, IrCl3 and MnCl3.
[0028] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is MnCl2, FeCl3, IrCl3 and SbCl5.
[0029] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is CoCl2·6H2O, FeCl3, RuCl3 and IrCl3.
[0030] According to an embodiment of the present invention, the metal precursor salts in the metal precursor salt solution include CoCl2·6H2O, SnCl2, RuCl3 and SbCl5.
[0031] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is VCl3, CoCl2·6H2O, PdCl2 and RuCl3.
[0032] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is CoCl2·6H2O, GaCl3, PdCl2 and IrCl3.
[0033] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is Cu(NO3)2·6H2O, CoCl2·6H2O, SbCl5 and K2PtCl6.
[0034] According to an embodiment of the present invention, the metal precursor salt in the metal precursor salt solution is NiCl2, Cu(NO3)2·6H2O, AlCl3 and PdCl2.
[0035] According to an embodiment of the present invention, the solvent in the metal precursor salt solution is deionized water.
[0036] According to an embodiment of the present invention, the temperature of the heating treatment is 50-200° C. The inventors found that a heating temperature in the range of 50-200° C. is conducive to the formation of porous foam.
[0037] According to an embodiment of the present invention, the temperature of the heating treatment is 120-200°C.
[0038] According to an embodiment of the present invention, the temperature of the heat treatment is 200°C, 180°C, 150°C, 145°C, 140°C, 135°C or 120°C.
[0039] According to an embodiment of the present invention, the heating treatment time is 0.1-200h.
[0040] According to an embodiment of the present invention, the heating treatment time is 5-24 hours.
[0041] According to an embodiment of the present invention, the heating treatment time is 5h, 12h, 14h, 18h or 24h.
[0042] According to an embodiment of the present invention, the calcination process is performed in an argon, nitrogen, ammonia or air atmosphere.
[0043] According to an embodiment of the present invention, the temperature of the calcination treatment is 300-1600° C. The inventors found that when the calcination temperature is within the range of 300-1600° C., C accumulation can be effectively avoided.
[0044] According to an embodiment of the present invention, the temperature of the calcination treatment is 400-650°C.
[0045] According to an embodiment of the present invention, the temperature of the calcination treatment is 650°C, 600°C, 550°C, 450°C or 400°C.
[0046] According to an embodiment of the present invention, the calcination treatment time is 0.1-2000h.
[0047] According to an embodiment of the present invention, the calcination treatment time is 12-48 hours.
[0048] According to an embodiment of the present invention, the calcination treatment time is 12h, 14h, 18h, 24h or 48h.
[0049] According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst is selected from MoSnMnIr metal oxide, MnFeIrSb metal oxide, CoFeRuIr metal oxide, CoSnRuBi metal oxide, VCoPdRu metal oxide, CoGaPdIr metal oxide, CuCoSbPt metal oxide or CuCoRuPt metal oxide.
[0050] In another aspect of the present invention, the present invention also proposes a method for preparing a bifunctional catalyst for an ultra-long life low-temperature zinc-air battery. According to an embodiment of the present invention, the housing comprises the following steps:
[0051] (1) adding a certain amount of metal precursor salt solution to a solution consisting of one or more thiourea / ammonium chloride / urea / ammonium sulfate and a starch / galactose / sucrose / fructose / glucose / maltose, and mixing them uniformly by means of magnetic stirring / mechanical stirring / ultrasound, etc.;
[0052] (2) placing the solution in (1) in a rotary oven and heating it until a large amount of dark brown loose porous material is produced;
[0053] (3) The obtained dark brown substance is calcined in an atmosphere such as argon / nitrogen / ammonia / air to obtain the catalyst.
[0054] According to an embodiment of the present invention, in step (1), the concentration of the metal salt is 0-100 mg / mL, and the ratio of easily decomposable ammonium salts (thiourea, ammonium chloride, urea, ammonium sulfate, etc.) to sugars (starch, galactose, sucrose, fructose, glucose, maltose, etc.) is 1:1-1:100 (mass ratio, unit mg).
[0055] According to an embodiment of the present invention, the temperature in step (2) is 50-200°C and the time is 0.1-200h.
[0056] According to an embodiment of the present invention, in step (3), the dark brown substance is calcined in an atmosphere such as argon / nitrogen / ammonia / air, with a calcination temperature of 300-1600° C. and a calcination time of 0.1-2000 h.
[0057] In another aspect of the present invention, the present invention also proposes the use of the low-temperature zinc-air battery bifunctional catalyst described above or the low-temperature zinc-air battery bifunctional catalyst prepared according to the method described above in preparing a battery.
[0058] According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst is used for electrocatalytic oxygen reduction and oxygen evolution reactions.
[0059] According to an embodiment of the present invention, the low-temperature zinc-air battery bifunctional catalyst is applied to a low-temperature zinc-air battery as an air electrode material.
[0060] According to an embodiment of the present invention, the present invention has at least one of the following advantages:
[0061] (1) The preparation method is simple, low-cost, environmentally friendly, and easy to scale up;
[0062] (2) By changing the content of different metals, the electronic structure of the catalyst can be regulated, thereby improving the OER and ORR performance of the catalyst;
[0063] (3) The catalyst is applied to the air positive electrode of the zinc-air battery. The assembled zinc-air battery not only has a high specific capacity and a large power density at low temperatures, but also has an ultra-long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0065] Figure 1 are SEM, TEM and HAADF-TEM images of the catalyst according to an embodiment of the present invention;
[0066] Figure 2It is a comparison diagram of dual-function curves and accelerated cycle stability test curves of the catalyst according to the embodiment of the present invention and the commercial Pt / C+IrO2 catalyst;
[0067] Figure 3 The performance of the battery at room temperature and low temperature when the catalyst according to the embodiment of the present invention and the commercial Pt / C+IrO2 catalyst are used as the positive electrode of the air electrode of the zinc-air battery. DETAILED DESCRIPTION
[0068] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0069] The raw materials used in the present invention are all commercially available analytically pure products and have not been purified.
[0070] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0071] Example 1
[0072] (1) Weigh a certain amount of (NH4)6Mo7O 24 4H2O, SnCl2, and IrCl3 were dissolved in deionized water to make the total concentration of metal salts 10 mg / mL.
[0073] (2) Then, ammonium salt (ammonium bicarbonate, ammonium carbonate) and galactose (the mass ratio of ammonium salt to galactose is 1:10, unit: mg) are added, and a uniform solution is formed by continuous stirring.
[0074] (3) The solution was then placed in a rotary oven at 140°C for 12 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0075] (4) Finally, the obtained brown substance was placed in a muffle furnace and calcined at 600°C for 18 hours to obtain MoSnIr ternary metal oxide.
[0076] Example 2
[0077] (1) Weigh a certain amount of MnCl2, FeCl3, IrCl3 and SbCl5 and dissolve them in deionized water so that the total concentration of the metal salts is 10 mg / mL.
[0078] (2) Then, ammonium salt (urea, ammonium carbonate) and galactose (the mass ratio of ammonium salt to galactose is 1:8, unit: mg) are added, and a uniform solution is formed by continuous stirring.
[0079] (3) The solution was then placed in a rotary oven at 120°C for 12 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0080] (4) Finally, the obtained loose porous black-brown material was placed in a tubular furnace and calcined at 400° C. for 24 h in an ammonia atmosphere to obtain MnFeIrSb metal oxide.
[0081] Example 3
[0082] (1) Weigh a certain amount of CoCl2·6H2O, FeCl3, RuCl3, and IrCl3 and dissolve them in deionized water so that the total concentration of the metal salts is 15 mg / mL.
[0083] (2) Then, ammonium salt (urea, ammonium carbonate) and glucose (the mass ratio of ammonium salt to sugar is 1:10, unit: mg) are added, and a uniform solution is formed by continuous stirring.
[0084] (3) The solution was then placed in a rotary oven at 135°C for 24 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0085] (4) Finally, the obtained loose porous black-brown material was placed in a tubular furnace and calcined at 550° C. for 18 h in a nitrogen atmosphere to obtain CoFeRuIr metal oxide.
[0086] Example 4
[0087] (1) Weigh a certain amount of CoCl2·6H2O, RuCl3, and SbCl5 and dissolve them in deionized water so that the total concentration of the metal salts is 20 mg / mL.
[0088] (2) Then, ammonium salt (urea and ammonium chloride) and sucrose (the mass ratio of ammonium salt to sugar is 1:15, unit: mg) are added, and a clear solution is obtained by continuous stirring.
[0089] (3) The solution was then placed in a rotary oven at 150°C for 18 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0090] (4) Finally, the obtained loose porous black-brown material was placed in a muffle furnace and calcined at 600° C. for 12 h in an air atmosphere to obtain CoRuBi metal oxide.
[0091] Example 5
[0092] (1) Weigh a certain amount of VCl3, CoCl2·6H2O, PdCl2, and RuCl3 and dissolve them in deionized water so that the total concentration of the metal salts is 10 mg / mL.
[0093] (2) Then, ammonium salt (ammonium bicarbonate and ammonium chloride) and glucose (the mass ratio of ammonium salt to sugar is 1:5, unit: mg) are added, and a clear solution is obtained by continuous stirring.
[0094] (3) The solution was then placed in a rotary oven at 145°C for 18 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0095] (4) Finally, the obtained loose porous black-brown material was placed in a muffle furnace and calcined at 550° C. for 14 h in an air atmosphere to obtain VCoPdRu metal oxide.
[0096] Example 6
[0097] (1) Weigh a certain amount of CoCl2·6H2O, GaCl3, PdCl2, and IrCl3 and dissolve them in deionized water so that the total concentration of the metal salts is 20 mg / mL.
[0098] (2) Then, ammonium salt (ammonium bicarbonate and urea) and glucose (the mass ratio of ammonium salt to sugar is 1:8, unit: mg) are added, and a clear solution is obtained by continuous stirring.
[0099] (3) The solution was then placed in a rotary oven at 200°C for 5 h to obtain a loose, porous, dark brown substance loaded with metal salts.
[0100] (4) Finally, the obtained loose porous black-brown material was placed in a muffle furnace and calcined at 450° C. for 48 h in an air atmosphere to obtain CoGaPdIr metal oxide.
[0101] Example 7
[0102] (1) Weigh a certain amount of CoCl2·6H2O, SbCl5 and K2PtCl6 and dissolve them in ionized water so that the total concentration of metal salts is 9 mg / mL.
[0103] (2) Then, ammonium salt (urea) and glucose (the mass ratio of ammonium salt to sugar is 1:20, in mg) are added, and a clear solution is obtained by continuous stirring.
[0104] (3) The solution was then placed in a rotary oven at 180°C for 14 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0105] (4) Finally, the obtained loose porous black-brown material was placed in a tubular furnace and calcined at 550° C. for 18 h in a nitrogen atmosphere to obtain CoSbPt metal oxide.
[0106] Example 8
[0107] (1) Weigh a certain amount of NiCl2, Cu(NO3)2·6H2O, AlCl3, and PdCl2 and dissolve them in ionized water so that the total concentration of the metal salts is 8 mg / mL.
[0108] (2) Then, ammonium salt (ammonium bicarbonate and urea) and lactose (the mass ratio of ammonium salt to sugar is 1:15, unit: mg) are added, and a clear solution is obtained by continuous stirring.
[0109] (3) The solution was then placed in a rotary oven at 150°C for 18 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0110] (4) Finally, the obtained loose porous black-brown material was placed in a tubular furnace and calcined at 650° C. for 24 h in a nitrogen atmosphere to obtain CuCoRuPt metal oxide.
[0111] Example 9
[0112] (1) Weigh a certain amount of SnCl2, CoCl2, MnCl2, and RuCl3 and dissolve them in ionized water so that the total concentration of the metal salts is 7 mg / mL.
[0113] (2) Then, ammonium salt (ammonium bicarbonate and urea) and glucose (the mass ratio of ammonium salt to sugar is 1:15, unit: mg) are added, and a clear solution is obtained by continuous stirring.
[0114] (3) The solution was then placed in a rotary oven at 150°C for 18 hours to obtain a loose, porous, dark brown substance loaded with metal salts.
[0115] (4) Finally, the obtained loose porous black-brown material was placed in a tubular furnace and calcined at 650°C for 24 hours under a nitrogen atmosphere to obtain SnCoMnRu metal oxide.
[0116] in, Figure 1 The morphology of the SnCoMnRu metal oxide prepared in Example 9 is characterized by the SEM image ( Figure 1 a) shows that the metal oxide is a porous foam-like substance. Figure 1 b) It can be seen that the foamy metal oxide is composed of tiny nanoparticles. HAADF-TEM ( Figure 1 c) shows that the metal oxide has good crystallinity.
[0117] Figure 2 The bifunctional ORR and OER performance of the SnCoMnR metal oxide prepared in Example 9 is characterized. From the lsv curve ( Figure 2 a) shows that the ORR and OER performance of the SnCoRu metal oxide are better than those of commercial Pt / C and IrO2 catalysts, respectively, and the oxygen potential difference is 0.628V, which is much better than the commercial Pt / C and IrO2 combination, showing excellent bifunctional catalytic properties. The SnCoMnR metal oxide has excellent OER stability. After 20,000 CV cycles, the overpotential remains basically unchanged ( Figure 2 b). The SnCoMnR metal oxide also has good ORR stability. After 200,000 CV cycles ( Figure 2 c), the half-wave potential changes slightly.
[0118] Figure 3 The performance of the zinc-air battery at room temperature and low temperature when the SnCoMnR metal oxide prepared in Example 9 is used as the air electrode material. Figure 3 It can be seen from the ac that when SnCoMnR metal oxide is used as the air electrode material, the performance at low temperature and room temperature is better than that of the battery with commercial Pt / C+IrO2 catalyst as the air electrode material. This proves that this SnCoMnR metal oxide has better performance as an air electrode at both low temperature and room temperature. Finally, the battery with this SnCoMnR metal oxide as the positive electrode was subjected to a long-term constant current charge and discharge cycle test at room temperature, and it can run for up to 1250h ( Figure 3 d), has excellent cycle stability. Figure 3 e and f show that the SnCoMnR metal oxide has a very good lifespan at low temperatures when used as the air electrode material, which is much better than the commercial Pt / C+IrO2 catalyst and has a very good lifespan at high currents (10 mA cm -2 ) can run stably for more than 700 hours.
[0119] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0120] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A low-temperature zinc-air battery bifunctional catalyst, characterized in that: The low-temperature zinc-air battery bifunctional catalyst comprises A 1-x-y-z B x C y D z O2, wherein A and B are independently selected from one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Sn, Ga, Ge, C and D are independently selected from one of Pt, Ir, Ru, Pd, Au, Ag, In, Sb, Tl, Pb, Bi, Nb, Mo, Cd, Among them, 0≦x<1, 0≦y<1, 0≦z<1, 0≦1-xyz<1, and at most one of x, y, z and 1-xyz is 0.
2. The low-temperature zinc-air battery bifunctional catalyst according to claim 1, characterized in that: The content of A is 0-99.9at%, the content of B is 0-99.9at%, the content of C is 0-99.9at%, and the content of D is 0-99.9at%, and at most one of the contents of A, B, C, and D is 0at%.
3. The low-temperature zinc-air battery bifunctional catalyst according to claim 1, characterized in that: The low-temperature zinc-air battery bifunctional catalyst is selected from MoSnMnIr metal oxide, MnFeIrSb metal oxide, CoFeRuIr metal oxide, CoSnRuBi metal oxide, VCoPdRu metal oxide, CoGaPdIr metal oxide, CuCoSbPt metal oxide or CuCoRuPt metal oxide.
4. A method for preparing a low-temperature zinc-air battery bifunctional catalyst, characterized in that: include: 1) mixing a metal precursor salt solution and a solution consisting of an ammonium salt and a sugar to obtain a mixed solution; 2) heating the mixed solution to obtain a porous material; 3) The obtained porous material is calcined to obtain the low-temperature zinc-air battery bifunctional catalyst.
5. The method according to claim 4, characterized in that The ammonium salt is one or more selected from ammonium bicarbonate, ammonium carbonate, thiourea, ammonium chloride, urea and ammonium sulfate; Optionally, the ammonium salt is ammonium bicarbonate and ammonium carbonate; Optionally, the ammonium salt is urea and ammonium carbonate; Optionally, the ammonium salt is urea and ammonium chloride; Optionally, the ammonium salt is ammonium bicarbonate and ammonium chloride; Optionally, the ammonium salt is ammonium bicarbonate and urea; Optionally, the sugar is selected from one of starch, lactose, galactose, sucrose, fructose, glucose and maltose; Optionally, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:1-1:100; Optionally, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:5-1:20; Optionally, the mass ratio of ammonium salt to sugar in the solution consisting of ammonium salt and sugar is 1:20, 1:15, 1:10, 1:8 or 1:5; Optionally, the mixing process is performed by magnetic stirring, mechanical stirring or ultrasound.
6. The method according to claim 4, characterized in that The concentration of the metal precursor salt solution is less than or equal to 100 mg / mL; Optionally, the concentration of the metal precursor salt solution is 8 mg / mL, 9 mg / mL, 10 mg / mL, 15 mg / mL or 20 mg / mL; Optionally, the metal precursor salt in the metal precursor salt solution is (NH4)6Mo7O 24 4H2O, SnCl2, IrCl3 and MnCl3; Optionally, the metal precursor salt in the metal precursor salt solution is MnCl2, FeCl3, IrCl3 and SbCl5; Optionally, the metal precursor salt in the metal precursor salt solution is CoCl2·6H2O, FeCl3, RuCl3 and IrCl3; Optionally, the metal precursor salts in the metal precursor salt solution are CoCl2·6H2O, SnCl2, RuCl3 and SbCl5; Optionally, the metal precursor salt in the metal precursor salt solution is VCl3, CoCl2·6H2O, PdCl2 and RuCl3; Optionally, the metal precursor salt in the metal precursor salt solution is CoCl2·6H2O, GaCl3, PdCl2 and IrCl3; Optionally, the metal precursor salt in the metal precursor salt solution is Cu(NO3)2·6H2O, CoCl2·6H2O, SbCl5 and K2PtCl6; Optionally, the metal precursor salt in the metal precursor salt solution is NiCl2, Cu(NO3)2·6H2O, AlCl3 and PdCl2; Optionally, the solvent in the metal precursor salt solution is deionized water.
7. The method according to claim 4, characterized in that The temperature of the heating treatment is 50-200°C; Optionally, the temperature of the heating treatment is 120-200°C; Optionally, the temperature of the heat treatment is 200°C, 180°C, 150°C, 145°C, 140°C, 135°C or 120°C; Optionally, the heating treatment time is 0.1-200h; Optionally, the heating treatment time is 5-24h; Optionally, the heating treatment time is 5 h, 12 h, 14 h, 18 h or 24 h.
8. The method according to claim 4, characterized in that The calcination treatment is carried out in an atmosphere of argon, nitrogen, ammonia or air; Optionally, the calcination temperature is 300-1600°C; Optionally, the calcination temperature is 400-650°C; Optionally, the calcination temperature is 650°C, 600°C, 550°C, 450°C or 400°C; Optionally, the calcination treatment time is 0.1-2000h; Optionally, the calcination treatment time is 12-48h; Optionally, the calcination treatment time is 12h, 14h, 18h, 24h or 48h.
9. The method according to claim 4, characterized in that The low-temperature zinc-air battery bifunctional catalyst is selected from MoSnMnIr metal oxide, MnFeIrSb metal oxide, CoFeRuIr metal oxide, CoSnRuBi metal oxide, VCoPdRu metal oxide, CoGaPdIr metal oxide, CuCoSbPt metal oxide or CuCoRuPt metal oxide.
10. Use of the low-temperature zinc-air battery bifunctional catalyst according to any one of claims 1 to 3 or the low-temperature zinc-air battery bifunctional catalyst prepared according to the method according to any one of claims 4 to 9 in preparing batteries.
Citation Information
Patent Citations
Bifunctional oxygen electrocatalyst and preparation and application thereof
CN112758996A
Bifunctional Oxygen Electrocatalyst, Preparation Method and Use Thereof
US20220190357A1